Problems and perspectives of environmental innovations implementation in an agricultural enterprise (Economics and region, 2022)
The article revealed that the implementation of eco-innovations has certain features, in particular, firstly, ecological innovations allow reducing the impact on the environment; secondly, environmental innovations go beyond the traditional organizational boundaries of innovation within the enterprise and allow to involve wider social mechanisms that cause changes in existing structures; thirdly, they relate to innovations in changing the composition of products, namely the production of products from environmentally friendly materials or secondary raw materials. It has been proven that enterprises that have chosen the European path of development must adhere to the principles and guidelines of European countries regarding the greening of agricultural enterprises, namely: sustainable development, which equally takes into account economic, social and ecological components; avoidance of negative impacts on the environment as a result of economic activity, taking into account remote impacts on the environment; rejection of projects that involve intervention in natural systems, if their impact on the environment is unpredictable. The authors determined that the main factors that motivate agribusiness to implement ecological innovations are the opportunity to reduce costs for the agricultural products production, risks of territory pollution, increase productivity and product quality, maximize efficiency, i.e. achieve environmental goals at minimum costs, reduce the cost of agricultural products, rational use natural resources, meeting the demand for ecologically clean products. It was found that enterprises that implement ecological innovations ensure sustainable development of the enterprise in the long term. And the result of the introduction of eco-innovations will be positive not only for the enterprise, but also directly for consumers, society and the state as a whole.
Keywords: management; sustainable development; ecological innovations; agribusiness; eco-innovative technologies